MENGHADIRKAN PEMBELAJARAN PARTISIPATIF MELALUI PEMBELAJARAN BERBASIS MASALAH PADA MATERI HAK DAN KEWAJIBAN DI SEKOLAH DASAR - Dhani Sutanti; Ratna Aulia Sani; Siti Hamidah Rohmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Civic education in schools plays a vital role in shaping students' character and helping them understand their rights and responsibilities within society. However, instructional practices that rely too heavily on the mere transmission of information often limit student participation and reduce opportunities for meaningful learning. This study employs Problem-Based Learning as an instructional approach to create a more participatory learning experience regarding the topic of rights and obligations. Contextual problems served as the starting point for learning activities within this classroom action research. Data were collected through classroom observations, learning outcome tests, and documentation throughout the instructional process. The results demonstrate positive changes in student engagement, including increased participation in discussions, greater confidence in expressing ideas, improved collaboration, and stronger involvement in problem-solving activities. These improvements contributed to better learning outcomes, as reflected by the rise in average achievement scores and mastery levels across the intervention stages. The findings indicate that the implementation of Problem-Based Learning makes instruction more effective in fostering student engagement during Civic Education lessons, while also rendering the learning process more contextual and meaningful for elementary school students.